Metafora Dalam Lagu “Bertaut” Karya Nadin Amizah (Kajian Stilistika) - Hopi Silviani; Rohanda Rohanda; Sofia Laila Rahmah (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2025)
This study employs a qualitative approach using a descriptive-analytical method to analyze the meanings and types of metaphors found in the lyrics of the song “Bertaut” by Nadin Amizah. This method was chosen because it allows the researcher to interpret data deeply within the linguistic and artistic context embedded in the lyrics. The main focus of the study lies in the process of identifying, classifying, and interpreting metaphorical expressions that represent complex emotional and aesthetic experiences. Data collection was carried out directly by the researcher through observation and note-taking techniques by carefully reading and examining the lyrics. All expressions with metaphorical potential were marked and collected for further analysis. The data analysis followed a systematic procedure consisting of intensive reading of the lyrics, identification of metaphorical forms, and classification based on Ullmann’s theory of metaphor. This theory provides a framework that includes several types of metaphors, such as anthropomorphic metaphors, animal metaphors, synesthetic metaphors, and abstract metaphors. The analysis identified seven metaphorical expressions in the song’s lyrics, reflecting the creative use of figurative language to convey profound emotional meanings. These metaphors were found to enrich the aesthetic value of the lyrics and enhance the expressive power of the song in depicting the singer’s inner experiences. Thus, the applied methodology not only reveals the structure of figurative language within the lyrics but also bridges the understanding of the complex meanings contained therein